Deconstruction of Islamic Scientific Authority: A Phenomenological Study on the Impact of Authentication Reduction Toward Pseudo Literacy Among Islamic University - Rabiha Maya Adiera; Eliwatis Eliwatis; Syahrur Ramli; Silfia Hanani; Salmiwati Salmiwati; Zulfani Sesmiarni; Nadia Zakia (Yayasan Darussalam Bengkulu, 2026)
The rapid integration of Artificial Intelligence (AI) in Islamic Higher Education Institutions (PTAI) has sparked a significant shift in how students engage with religious knowledge. This study investigates the deconstruction of Islamic scientific authority, focusing on the impact of authentication reduction toward